Liderança transformadora e os níveis de consciência corporativa: estudo de caso em empresas do ramo de varejo - Cavalcanti, Vera Lucia dos Santos (2004)
This research focus on the Leadership and its contribution to reach organization s results. The research is based on bibliographic revision and it dissertates about evolutive management models and the evolution of leadership roles in the last hundred years. The results of the research in the study case, were presented through transcription of employees statements from the researched organization, analysis and conclusions. The analysis of the results shows perception of the employees in relation to the level of corporative consciousness . The conclusions point to the fact that Leadership plays a central role to the success of the organization which is concerned with social and environmental compromise and with employee s development